Optimalisasi Peran Lembaga Adat Dan Perangkat Nagari Dalam Pencegahan Stunting Di Nagari Batang Arah Tapan - Slamet Riyadi; Ahmad Khairul Nuzuli; Winda Oktaviana (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Stunting is a developmental disorder experienced by children due to malnutrition, repeated infections, and inadequate psychosocial stimulation. several factors that influence the incidence of lack of access to nutritious food, low intake of vitamins, minerals, and sources of animal protein, lack of health facilities and clean water sources. This service uses the Participatory Rural Appraisal (PRA) Method or Participatory Understanding of Rural Conditions, which is an approach and method that allows the community to jointly analyze life's problems in order to formulate real plans and policies. from this dedication it is known that only 1 toddler was affected by stunting in Nagari Batang Arah Named Saka Septria Age 1 Year. Stutting children are already under the supervision of the Community Empowerment Service and the Population Control Village for Family Planning.